Expression and cellular distribution of insulin-like growth factor 1 receptor during window of implantation in infertile women with intramural fibroids - Makker, Annu; Goel, Madhu Mati; Nigam, Dipti; Pandey, Amita (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Background: The “window of implantation” (WOI) is a transient but well defined period during which the hostile endometrial lining is transformed to a surface receptive to accept the embryo. Recently, data are beginning to accumulate suggesting negative influence of non-cavity distorting intramural uterine fibroids (NCD-IMF) on endometrial receptivity that may have implications for implantation failure. However, molecular mechanisms underlying infertility associated with NCD-IMF remain unclear. The aim of present study was to examine the expression and cellular distribution of insulin-like growth factor 1 receptor (IGF1R) during WOI in infertile women with NCD-IMF and fertile controls. While, reports are available that support role of IGF1R in mediating adhesive interaction with the implanting blastocyst, the effect of NCD-IMF on IGF1R expression during the WOI is not defined. Methods: Quantitative real-time polymerase chain reaction and immunohistochemistry were used to evaluate messenger RNA (mRNA) and protein expression of IGF1R in midsecretory endometrial biopsies obtained from infertile women with NCD-IMF (n=20) and healthy fertile controls (n=10). Results: As compared to fertile controls, significantly higher IGF1R: i) mRNA levels (1.59 fold up regulation; p=0.044) and ii) immunoscore in the luminal epithelium (8.94±3.13 versus 6.31±1.49; p=0.009) were observed in infertile women with NCD-IMF. Conclusions: Over expression of IGF1R in infertile women with NCD-IMF, during the window of receptivity, may result in altered ability of uterine epithelial cells for blastocyst adhesion and subsequent implantation, which might lead to poor reproductive outcome in these women.